Prevalence of carpal tunnel syndrome in patients with long-term type 2 diabetes mellitus - Defu Dong; Hongwei Liu (Heliyon, 2022)
Generally, Carpal tunnel syndrome (CTS) is more common in diabetes mellitus (DM), especially in subjects with coexisting diabetic polyneuropathy (DPN) and/or long-term DM. Based on the analysis of nerve conduction velocity (NCV), the prevalence of CTS and the features of nerve injury were retrospectively explored in type 2 diabetes mellitus (T2DM) patients. In this cohort, there were 353 T2DM patients who were hospitalized in Taiyuan Central Hospitalbetween January 2018 and January 2019. The pathological rates of NCVs between the left and right median nerves were compared, including the gender effect. The examinations were mainly directed to analyze the median nerve injury features. Among 353 patients, 139 patients (39.3%) presented with CTS. These 139 T2DM patients with CTS were then divided into groups based on the nerve injury location and injured nerve type. The prevalence of sensory nerve injury (SNI) was higher than that of motor nerve injury (MNI). The CTS patients had a significantly higher occurrence rate of SNI than MNI (P < 0.05). The abnormal rate of sensory nerve conduction velocity (SCV, P = 0.01) and motor nerve conduction velocity (MCV, P < 0.05) were higher in the right median nerve. No significant differences were detected for other nerves on either side. Significant differences in abnormal rates of SCV of the left (P = 0.04) and the right (P = 0.03) median nerves between the two genders were found. There were no significant abnormalities for other nerves on either side and either gender. Early screening of NCV is needed for T2DM patients to detect CTS with a high prevalence rate. This study suggests that early detection of NCV can identify CTS in the absence of clinical conditions and SNI may occur earlier in long-term T2DM patients with CTS.